Trends in Materials Science for Ligament Reconstruction - Roxana Sava, Oana; Florin Sava, Daniel; Radulescu, Marius; Georgiana Albu, Madalina; Ficai, Denisa; Fernanda Veloz-Castillo, Maria; Angel Mendez-Rojas, Miguel; Ficai, Anton (Current Stem Cell Research & Therapy, 2017)
The number of ligament injuries increases every year and concomitantly the need for materials or systems that can reconstruct the ligament. Limitations imposed by autografts and allografts in ligament reconstruction together with the advances in materials science and biology have attracted a lot of interest for developing systems and materials for ligament replacement or reconstruction. This review intends to synthesize the major steps taken in the development of polymer-based materials for anterior cruciate ligament, their advantages and drawbacks and the results of different in vitro and in vivo tests. Until present, there is no successful polymer system for ligament reconstruction implanted in humans. The developing field of synthetic polymers for ligament reconstruction still has a lot of potential. In addition, several nano-structured materials, made of nanofibers or in the form of ceramic/polymeric nanocomposites, are attracting the interest of several groups due to their potential use as engineered scaffolds that mimic the native environment of cells, increasing the chances for tissue regeneration. Here, we review the last 15 years of literature in order to obtain a better understanding on the state-of-the-art that includes the usage of nano- and poly-meric materials for ligament reconstruction, and to draw perspectives on the future development of the field.
Keywords: ligaments